(untitled) (CIPEEX, 2025)
Objectives: The aging process is associated with a reduction in immune response. However, it is unknown to what extent resistance training can modulate this response in older adults. Method: A randomized clinical trial was conducted at the Evangelical University of Goiás (UniEVANGÉLICA), where older adult volunteers (aged 60 to 85 years) were randomized (n = 40/group) into a control group (no physical training) and a training group (physical training only). The training protocol was carried out for 3 months, with moderate intensity, 3 sessions per week, lasting approximately 50-60 minutes. Assessments were performed before the start of the protocol and after 3 months. Pulmonary immune response was assessed by measuring pro-inflammatory cytokines (IL-6 and TNF-alpha) and anti-inflammatory cytokines (IL-10 and Klotho) in exhaled breath condensate, in addition to nitric oxide levels in exhaled air (FeNO). The analyses were expressed as mean and standard deviation. A significance level of p≤0.05 was adopted for comparisons performed in the paired t-test and for multiparametric analyses. Results: The results showed that resistance training resulted in a significant decrease in the levels of pro-inflammatory cytokines IL-6 (p<0.0001) and TNF-alpha (p<0.043), while increasing levels of the anti-inflammatory cytokine IL-10 (p<0.0003) and Klotho (p<0.0001). In addition, resistance training increased nitric oxide levels in exhaled air (p<0.0072) but levels remained within normal limits. Conclusions: Resistance training resulted in a decrease in pro-inflammatory pulmonary biomarkers and an increase in anti-inflammatory pulmonary biomarkers, demonstrating its usefulness in strengthening the pulmonary immune system.